Indonesia’s Economic Development Cooperation Program Through Private Public Partnership (PPP) Scheme - Park, Jongmin; Firman, Aries F (The Indonesian Journal of Business Administration, 2015)
Abstract.This Project is the study of how Low and Middle Income Countries (LMICs) overcome Middle Income Trap (MIT). This study selects Indonesia as an example representing LMIC and suggests Private Public Partnership (PPP) method as a key solution to overcome MIT. The study also finds the methodology to contribute to Indonesia’s economic development through International Development Cooperation (IDC). This study provides Research Questions in the beginning and comes to conclusion as the answer to the Questions through Analysis Framework. It is based on Qualitative Methodology using expert group interview and document review. Besides, as the Final Project of Master of Business Administration (MBA), it recommends the realistic application and practical implementation.In the first stage, this Project analyzes the current status of PPP in Indonesia and finds application problems of PPP tools. It also delves deeply into the characteristic and varieties of PPP projects through literature investigation as well as the opinions from experienced experts in the field of PPP. In the second stage, this project uses analytical tool of interpretation and discussions of business theory. From the work, applicable and meaningful results are drawn. In addition, the results are reviewed and refined for practical application.In the last stage, it endeavors to apply to a real IDC program. It recommends IDC’s contribution and suggestion for the success of PPP project. Finally it shows the vision of economic development in Indonesia through using PPP scheme.For the reference, PPP is normally an acronym for Public Private Partnership, but in this project, PPP is used as an acronym for Private Public Partnership stressing importance of private sector in terms of economic development.Key words: Low and Middle Income Countries (LMIC), Middle Income Trap (MIT), Private Public Partnership (PPP) tools, International Development Cooperation (IDC) program